Trophic connectivity between offshore upwelling and the inshore food web of Banc d'Arguin (Mauritania): New insights from isotopic analysis. (5th November 2015) - Carlier, Antoine; Chauvaud, Laurent; van der Geest, Matthijs; Le Loc'h, François; Le Duff, Michel; Vernet, Marc; Raffray, Jean; Diakhaté, Djibril; Labrosse, Pierre; Wagué, Abdoulaye; Le Goff, Clément; Gohin, Francis; et al.
Abstract: Banc d'Arguin (BA), Mauritania, is a nationally protected shallow gulf > 10, 000 km 2 between the Sahara desert and the upwelling system off the Mauritanian coast. In the southeast, BA consists of a 500 km 2 tidal flat, the most important wintering site for shorebirds using the East Atlantic Flyway. The Mauritanian upwelling-driven phytoplankton production supports the most productive fisheries worldwide, but little is known about its trophic role in the functioning of the inshore BA food web. Using stable isotopes as trophic tracers to distinguish between upwelling-driven phytoplankton, open ocean phytoplankton, and benthic primary producers, we assessed the spatial extent to which the inshore BA food web is fuelled by upwelling-driven phytoplankton production. The δ 13 C and δ 15 N signals were characterized in dominant primary producers, benthic invertebrate taxa, and various fish species along an offshore–inshore (northwest–southeast) gradient. We also monitored the spatial and temporal extent of upwelling entering BA during 2008 with remote sensing of sea surface temperature and chlorophyll a data. The results suggest that benthic invertebrates and fishes living in the northwestern part of BA depend on the nearby upwelling phytoplankton production, but this food source does not support the intertidal benthic community in southeast BA. Furthermore, the isotopic signatures of fishes suggest weak trophic connectivity between the northern subtidal and southeastern intertidal BA. Our results support the hypothesis that the southeastern tidal flat region functions as a distinct ecosystem with a food web supported mainly by local benthic primary production, which is crucial knowledge for effective management of the pristine BA national park. Highlights: The Mauritanian upwelling only fuels the northwestern part of Banc d'Arguin food web. Coupling remote sensing with stable isotope analysis to infer trophic connectivity. Vast seagrass-covered intertidal flat supported by local benthic primary production. Weak connectivity between the northern and southern fish assemblages of Banc d'Arguin.